Docking studies and molecular dynamics simulation of ipomoea batatas L. leaves compounds as lipoxygenase (LOX) inhibitor - Yeni, Y. (Wolters Kluwer Medknow Publications, 2020)
Background: Inflammatory mediators produced by cyclooxygenase (COX) and lipoxygenase (LOX) pathways are responsible for many human diseases, such as cancer, arthritis, and neurological disorders. Flavonoid-containing plants, such as Ipomoea batatas leaves, have shown potential anti-inflammatory activity. Objectives: This study aimed to predict the actions of 10 compounds in I. batatas leaves, which are YGMâ0a cyanidin 3â0âsophorosideâ5â0âglucosede, YGMâ0f cyanidin 3âOâ(2â0â(6â0â(E)âpâcoumaroylâÎ²âDâg l u c o p y r a n o s y l) â Î² â D â g l u c o p y r a n o s i d e) â 5 â 0 â Î² â D â g l u c o p y r a n o s i d e , YGMâ1a cyanidin 3â(6,6â²âcaffeylpâhydroxybenzoylsophoroside) â5âglucoside, YGMâ1b cyanidin 3â(6,6â²âdicaffeylsophor-oside)â5âglucoside, YGMâ2 cyanidin 3â(6âcaffeylsophoroside)â5âglucoside, YGMâ3 cyanidin 3â(6,6â²âcaffeyl-ferulylsophoroside)â5âglucoside, YGMâ4b peonidin 3â(6,6â²âdicaffeylsophoroside)â5â glucoside, YGMâ5a peonidin 3â(6,6â²âcaffeylphydroxybenzo-ylsophoroside)â5âgluco-side, YGMâ5b cyanidin 3â6âcaffeylsophoroside)â5âglucosede, and YGMâ6 peonidin 3â(6,6â²âcaffeylferulylsophoroside)â5âglucoside as LOX inhibitors, and also predict the stability of ligandâLOX complex. Materials and Methods: The compounds were screened through docking studies using PLANTS. Also, the molecular dynamics simulation was conducted using GROMACS at 310 K. Results: The results showed that the most significant binding affinity toward LOX was shown by YGMâ0a and YGMâ0a, and the LOX complex in molecular dynamics simulation showed stability for 20 ns. Conclusion: Based on Docking Studies and Molecular Dynamics Simulation of I. Batatas Leaves compounds, YGM-0a was shown to be the most probable LOX inhibitor. Â© 2020 Wolters Kluwer Medknow Publications. All rights reserved.